Algorithm to select optimal systemic anti‐psoriatic drugs in relation with patients' Psoriasis Area and Severity Index score for plaque psoriasis. Issue 6 (24th November 2015) - Bae, Soo Hyeon; Yun, Sook Jung; Lee, Jee‐Bum; Kim, Seong‐Jin; Won, Young Ho; Lee, Seung‐Chul
Abstract: This study sought to develop a therapeutic algorithm for selecting the optimal systemic drugs to treat moderate to severe psoriasis, based on the patient's Psoriasis Area Severity Index (PASI) score. Data from 191 patients undergoing treatment for plaque psoriasis were retrospectively analyzed. Pre‐ and post‐treatment PASI scores were compared across patients treated with acitretin of retinoic acid (RA; n = 95), methotrexate (MTX; n = 41) or cyclosporin A (CsA; n = 55). The PASI score improvement was examined at weeks 4 (primary end‐point) and 12 (secondary end‐point). MTX and CsA had a higher global therapeutic efficacy, with more patients exhibiting a marked improvement (≥75% improvement in PASI [PASI 75]) at week 12 with MTX (56.1%, P = 0.028) and CsA (54.5%, P = 0.025) than RA (35.8%). Multivariate analysis adjusting for confounders produced consistent results ( P = 0.026). For patients with severe psoriasis (PASI >12), the PASI 75 response was higher with CsA (55.6%) than RA (31.5%) ( P = 0.023) at week 4 and higher with MTX (57.1%, P = 0.029) and CsA (61.5%, P = 0.017) than RA (21.7%) at week 12. Because RA is a standard systemic drug, the RA group was divided into two subgroups based on the PASI 50 response at week 12. Marked or moderate improvement (PASI ≥50) with RA was observed in patients with a pretreatment PASI score less than 14. Thus, oral RA is recommended as a first‐line drug for patients with PASI of less than 14, and MTX or CsA are recommended for patients with PASI of 14 or more.